REAKTUALISASI TEMBANG DOLANAN JAWA DALAM RANGKA PEMBENTUKAN KARAKTER BANGSA (KAJIAN SEMIOTIK) - Nugrahani, Farida (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this study to describe (1) the meaning of song dolanan Java, (2) the values of local knowledge (local wisdom) in songs such as forming the national character, and (3) the renewal of the song is in the context of the formation of the nationâs character. Data in this descriptive qualitative study, collected through a literature review, interviews, and observation, from the sources, texts, and events. Data analysis was performed by inductively interactive models. For the meaning of Java dolanan song used method of reading a model consisting of a semiotic reading of the heuristic and hermeneutic (retroactive). The results showed that: (1) Tembang dolanan Java has the meaning that is loaded with moral messages that are important to the formation of national character, (2) The value of local wisdom in dolanan songs like âIlir-Ilirâ, âSluku-Sluku Bathokâ, âJaranan â, and others are noble universal values as in the nine pillars of character, (3) the value of local wisdom in the song is worth direaktualisasikan dolanan Java in order to character formation, which according to the nationâs cultural roots. That is an important issue, because our nation is known for friendly, tolerant, polite and religious as the prototype of the proud nation of East and West are contrasted with the selfish, individualistic, hedonistic, and secular, as if living myth. Noble culture of the nation is now experiencing a shift due to the rise of foreign cultures in a global era life. With the expectation that the investment value of local wisdom through song dolanan renewal to be effective, needs to be implemented through the Java language learning (local charge) at the school from elementary, middle to upper.